Allergic Inflammation Caused by Dimerized Translationally Controlled Tumor Protein is Attenuated by Cardamonin - Pyun, Haejun; Nam, Joo-Won; Cho, Hyunsoo; Park, Jiyoung; Seo, Eun Kyoung; Lee, Kyunglim (Frontiers in Pharmacology, 2021)
We demonstrated in our previous reports that dimeric form of translationally controlled tumor protein (dTCTP) initiates a variety of allergic phenomena. In the present study, we examined whether and how dTCTP’s role in allergic inflammation can be modulated or negated. The possible potential of cardamonin as an anti-allergic agent was assessed by ELISA using BEAS-2B cells and OVA-challenged allergic mouse model. The interaction between cardamonin and dTCTP was confirmed by SPR assay. Cardamonin was found to reduce the secretion of IL-8 caused by dTCTP in BEAS-2B cells by interacting with dTCTP. This interaction between dTCTP and cardamonin was confirmed through kinetic analysis (KD = 4.72 ± 0.07 μM). Also, cardamonin reduced the migration of various inflammatory cells in the bronchoalveolar lavage fluid (BALF), inhibited OVA specific IgE secretion and bronchial remodeling. In addition, cardamonin was observed to have an anti-allergic response by inhibiting the activity of NF-κB. Cardamonin exerts anti-allergic anti-inflammatory effect by inhibiting dTCTP, suggesting that it may be useful in the therapy of allergic diseases.